Causes of resistant hypertension detected by a standardized algorithm - Limonta, Livia Beatriz Santos [UNESP] (2012)
Resistant hypertension (RH) is characterized by blood pressure above 140 × 90 mm Hg, despite the use, in appropriate doses, of three antihypertensive drug classes, including a diuretic, or the need of four classes to control blood pressure. Resistant hypertension patients are under a greater risk of presenting secondary causes of hypertension and may be benefited by therapeutical approach for this diagnosis. However, the RH is currently little studied, and more knowledge of this clinical condition is necessary. In addition, few studies had evaluated this issue in emergent countries. Therefore, we proposed the analysis of specific causes of RH by using a standardized protocol in Brazilian patients diagnosed in a center for the evaluation and treatment of hypertension. The management of these patients was conducted with the application of a preformulated protocol which aimed at the identification of the causes of resistant hypertension in each patient through management standardization. The data obtained suggest that among patients with resistant hypertension there is a higher prevalence of secondary hypertension, than that observed in general hypertensive ones and a higher prevalence of sleep apnea as well. But there are a predominance of obesity, noncompliance with diet, and frequent use of hypertensive drugs. These latter factors are likely approachable at primary level health care, since that detailed anamneses directed to the causes of resistant hypertension are applied. © 2012 Livia Beatriz Santos Limonta et al.